(untitled) (Research, Society and Development, 2022)
Objective: To map the scientific evidence of the practices used by nurses for ultrasound-guided PICC puncture in neonates in intensive care. Methodology: Scope review protocol, structured according to the Joanna Briggs Institute methodology and checklist of the Preferred Reporting Items for Systematic reviews and Meta-Analyses extension for Scoping Reviews, filed and registered in the Open Science Framework via the link: https:/ /osf.io/hzd9w/. The identification of relevant documents will be carried out in five bibliometric resources and the exploration of gray literature from the Brazilian Digital Library of Theses and Dissertations database. Two evaluators will select the data from the included material, which answer the research question: What are the practices used for ultrasound-guided epicutaneous catheter puncture in critically ill neonates? Results: The results of this review will be summarized and presented in tables or figures and discussed in a descriptive analytical manner. Final Considerations: The aim is to map the evidence and the practices used by nurses in the puncture of the PICC catheter guided by ultrasound in neonates, so that they can contribute to advances in care management, both in the management and care spheres.